Exploring Trends and Future Paths in Tourism Villages Research: An Intellectual Mapping - Wahyoedi, Soegeng; Hermawan, Budi; Wijaya , Adi; Setyowati , Lis (Journal of Ecohumanism, 2024)
Sustainable tourism development in rural villages requires in-depth literature exploration. Bibliometric analysis reveals new themes and trends in village tourism research. The use of strategic diagrams enhances understanding of sustainable tourism research, particularly in rural villages. This approach uncovers new research opportunities and areas for future studies. Researchers searched the WOS database for rural tourism and tourist villages, focusing on scholarly journal publications from 2014 to 2023 in English. They employed advanced bibliometric techniques to examine the changing landscape of village and rural tourism research. Key identified themes include place attachment, traditional villages, and destination image. The analysis shows the importance of interdisciplinary approaches in creating sustainable tourism strategies, with a focus on understanding emotional ties to destinations and enhancing the significance of traditional villages. Future research should integrate cultural, social, and environmental dimensions into village tourism development, involving tourists in creating memorable experiences. The research underscores the significance of holistic and interdisciplinary approaches in promoting sustainable development. Nevertheless, constraints encompass scant bibliographic information, regional partiality, and inadequate examination of stakeholders' viewpoints regarding sustainable tourism growth.